PENGGUNAAN KERTAS DALUANG SEBAGAI MEDIA CETAKALTERNATIF - Priscilla Panti Meyrina (DeKaVe, 2012)
These thingsthat happened as a result too many consumption plastic was to be a concern bythemselves in society at large. Concern and fear a threat disasters as a result pollution from the land mustbe reduced to reduce danger environmental pollution, so we need to be innovative a to reduce the usematerials as vinyl print media, especially among university students ViSual Communication Design.Because it is meant for the students, and innovation must be cheaper and can be found easily.Paper use sustains daluang as a replacement for vinyl to score a material works, can become oneof the problem solution that can be caused by the use of material vinyl excessively.Keyword: Paper daluang, environmentally friendly, innovation alternative printed media.